Age cohort effects on unemployment in the USA: Evidence from the regional level - Carsten Ochsen (Papers in Regional Science, 2021)
Since the early 1970s, it was argued that shifts from relatively smaller to larger youth cohorts in the labor force raise the unemployment rate. In contrast, using US state-level data, two studies come to a contrary conclusion. I provide a theoretical framework for local labor markets that considers age cohort differences in labor market characteristics. Using a spatial panel data model and US county-level data (2000–2014), the estimates provide strong evidence that aging of the working-age population reduces overall unemployment by almost 1 percentage point. Long-run effects that consider local feedbacks are even larger.
Keywords: 300; aging; regional unemployment; spatial interactions